PAYMENTS ADMINISTRATION SYSTEM S.P.P. IN ELEMENTARY SCHOOL MIDSHIPMAN NATION, CIPUTAT USING MICROSOFT VISUAL BASIC 6.0. - Derry Kharisma Wim; Erick Orlando, SKom, MMSI Erick Orlando, SKom, MMSI (Jurnal Sistem Informasi, 2010)
This study explains the writing of the administration system of payment of fees inelementary school. Cadets Nations, Ciputat that during this process is done manually.Therefore the writer create the administrative system of payment of fees using acomputerized system using Microsoft Visual Basic 6.0 and Databases usingMicrosoft Access.Hopefully this writing has become an alternative for the school and to its employeeswho expect all their activities are operating effectively, efficiently and coordinated.